A Regulatory and Economic Perplexity: Bitcoin Needs Just a Bit of Regulation - Daniela Sonderegger (Washington University Journal of Law & Policy, 2015)
The use of Bitcoin as an alternative to traditional “flat” currency is “unnerving precisely because a world where it is used for all transactions is one where the ability of a central bank to guide the economy is destroyed, by design.” Bitcoin, the first decentralized digital currency, is a peer-to-peer payment system that allows international transactions to take place at any hour and in any place for very low cost. This Note analyzes Bitcoin and ultimately proposes a short-term solution to Bitcoin’s regulatory uncertainty that aims to strike a balance between the government’s interest in regulation and Bitcoin’s rejection of central authority – a loosely defined legal framework that operates with a minimal degree of governmental intervention.
Keywords: Bitcoin; currency regulation